Training and hormonal variability in a Premier League soccer team - de Vita, F.; Dorizzi, R.; Corradini, G.; Caruso, B. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Fitness of the athletes is considered the product of the External Training Load (ETL) and the Internal Training Load (ITL). The ETL is the complex of stimula characterizing the different phases of training and improves the athlete`s performance. The ITL is the assessment of the metabolic work induced in athletes by training and its analysis allows to measure the physiologic and psychological effects. The relationship between ETL and ITL allows to evaluate athletes` conditions by tuning load and recovery phases. The Cortisol/Free Testosterone Ratio (CFTR) has been reported as the best among the many tests proposed in the past to assess ITL. In this study we investigated CTFR in 82 premier league soccer players between July 2002 and April 2006. 538 blood samples have been drawn in 22 different sessions (mean: 6.56 each; in 11 athletes at least 16 samples have been collected and this subgroup proved to be statistically representative of the whole team). In the first 3 seasons we observed a consistent pattern of the CFTR; a CFTR peak is shown immediately after the summer training followed by a gradual decrease during the championship and a further peak in the next summer. In the last season analyzed, (2005-2006) in which ETL has been administered using a different methodology, we find some meaningful differences. Really, while in the first 3 seasons the ETL has been homogenously administered to the soccer players, in the last season, ETL has been administered on the basis of work intensity. The two different conditioning methodologies yielded similar mean (±SD and) lowest CFTR levels (respectively 0.100±0.026 vs 0.108±0.031 and 0.062 vs 0.058), while the maximum levels showed a significant difference (0.165 vs 0.188; p <0.05). Furthermore, CFTR is very variable in the homogenously trained soccer players; CTFR is much more stable in the players individually trained. In conclusion ETL changes in administering the work load influences CFTR keeping it within ±30% oscillations which is, according to our experience, the reference limits. Therefore, in our opinion, CFTR is an effective index of the correlation between ETL and ITL by means of the work load and intensity.